2003
DOI: 10.1111/j.1432-2277.2003.tb00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of cryptococcosis in adult solid-organ transplant recipients

Abstract: While studies in kidney recipients have found meningitis to be the most common clinical manifestation of cryptococcosis (Cry), it is unclear if the clinical presentation of Cry differs among various solidorgan transplant (SOT) recipients and whether the serum cryptococcal antigen (SCA) might predict the site of infection. We report the clinical manifestations and the correlation with a positive SCA among 55 consecutive SOT recipients diagnosed with Cry at the University of Pittsburgh Medical Center. These incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 23 publications
6
48
0
4
Order By: Relevance
“…The opposite has been seen in liver transplantation (Singh 2000). The main risk factor related to the development of cryptococcosis after solid organ transplantation is the immunosuppressive regimen, particularly the use of corticosteroid drugs (Vilchez et al 2002(Vilchez et al , 2003. In contrast to kidney recipients, most liver recipients are no longer receiving corticosteroid drugs during the late post-transplant period, a time when higher incidences of cryptococcosis have been observed.…”
Section: Discussionmentioning
confidence: 97%
“…The opposite has been seen in liver transplantation (Singh 2000). The main risk factor related to the development of cryptococcosis after solid organ transplantation is the immunosuppressive regimen, particularly the use of corticosteroid drugs (Vilchez et al 2002(Vilchez et al , 2003. In contrast to kidney recipients, most liver recipients are no longer receiving corticosteroid drugs during the late post-transplant period, a time when higher incidences of cryptococcosis have been observed.…”
Section: Discussionmentioning
confidence: 97%
“…[30][31][32][33][34][35][36] The sensitivity of serum Ag was higher than that of blood cultures (87% vs 42%), and it was higher in AIDS patients (in whom disseminated disease with fungemia is most frequently observed) when compared with non-HIV immunocompromised subjects (95% vs 77%). However, data on non-HIV patients are mainly derived from solidorgan transplant recipients 33,36 and the few data available in hemato-oncological patients do not allow separate performance analyses. 32,35 In Cryptococcus meningitis, the sensitivity of both CSF Ag testing and culture was very high (97%).…”
Section: Cryptococcus Agmentioning
confidence: 99%
“…In one study, heart transplant patients were more likely than other solid organ groups to develop cryptococcosis, but kidney transplant recipients were most likely to have disseminated disease. This study also showed that serum cryptococcal antigen was not always helpful in identifying isolated pulmonary Cryptococcus infection; 82% of patients with cryptococcal pneumonia had a negative serum cryptococcal antigen [55]. …”
mentioning
confidence: 75%
“…In one study of SOT recipients with cryptococcosis, the median time to diagnosis in lung, heart, and kidney transplant recipients was 210, 450, and 630 days, respectively [55]. In the TRANSNET cohort, median time to diagnosis of cryptococcosis was 575 days.…”
Section: Ifi Timeline: Sotmentioning
confidence: 99%